ROMANUL LIDIEI ISTRATI TOT MAI DEPARTE… AMÂNAT EDITORIAL - CIORTAN, Ecaterina (BIBLIOPOLIS, 2020)
The author analyses the novel Tot mai departe by Lidia Istrati (1941-1997). The novel was a result of author’s historical researches about the personality of the prince Stefan cel Mare and his presence in Bessarabian social and cultural contexte. The action of the novel takes place during the years 1467-1473, years of brilliant victories of Stefan cel Mare on the Hungarians at Baia Mare and the Tatars at Lipnic, but also heavy meditations on destiny and personality of the community. The writer tries to break away from dull reality of the time in which he lived, studying depth annals people to write the novel, dedicated to prince Stefan cel Mare, epic canvas on which he worked about ten years. The novel published stayed for four years in the magazine Nistru editorial office, then another five years at the publishing house „ Literatura Artistică „.